การวิจัยเชิงปฏิบัติการเพื่อพัฒนาศักยภาพการผลิตโคนม จังหวัดสกลนคร - อัมภาผล รองศาสตราจารย์ ดร.หาญชัย (Journal of Graduate School Sakon Nakhon Rajabhat University, 2017)
การวิจัยเชิงปฏิบัติการเพื่อพัฒนาศักยภาพการผลิตโคนมจังหวัดสกลนคร The Action Research for Potential Development of Diary Production in Sakon Nakhon Province บทคัดย่อ การวิจัยครั้งนี้มีความมุ่งหมายเพื่อ 1) ศึกษาสภาพและปัญหาในการเลี้ยงโคนม จังหวัดสกลนคร 2)หาแนวทางพัฒนาศักยภาพการผลิตโคนม จังหวัดสกลนคร 3) ศึกษาผลการพัฒนาศักยภาพการผลิตโคนมของเกษตรกร จังหวัดสกลนคร โดยใช้การวิจัยเชิงปฏิบัติการ (Action Research) กลุ่มเป้าหมายของการวิจัยครั้งนี้ คือ กลุ่มผู้ร่วมวิจัย จำนวน 5 คน และกลุ่มผู้ให้ข้อมูล จำนวน 30 คน เครื่องที่ใช้ได้แก่ แบบทดสอบ แบบสอบถาม แบบสังเกต แบบสัมภาษณ์แบบมีโครงสร้าง และแบบประเมินผลการประชุมเชิงปฏิบัติการ การวิเคราะห์ข้อมูลเชิงปริมาณใช้สถิติ ค่าเฉลี่ย ค่าร้อยละ ค่าเบี่ยงมาตรฐาน และร้อยละความก้าวหน้า การตรวจสอบข้อมูลเชิงคุณภาพ ผู้วิจัยได้ทำการวิเคราะห์เนื้อหา (Content analysis) จัดหมวดข้อมูลและนำเสนอข้อมูลเชิงพรรณนาวิเคราะห์ ผลการวิจัยพบว่า 1. ผลการศึกษาสภาพและปัญหาการเลี้ยงโคนม จังหวัดสกลนคร ปรากฏผลดังนี้ 1.1 สภาพ การผลิตโคนมของเกษตรกร จังหวัดสกลนคร มีสมรรถภาพการผลิตต่ำ สังเกตได้จากตัวชี้วัด คือ ปริมาณน้ำนม องค์ประกอบน้ำนม และความสมบูรณพันธุ์ 2.1 ปัญหา เกษตรกรยังขาดความรู้ ความเข้าใจในการเลี้ยงโคนม เช่น การคัดเลือกและการผสมพันธุ์ อาหารและการให้อาหาร การจัดการสุขาภิบาลและการป้องกันโรค จึงทำให้มีผลกระทบต่อการให้ผลผลิตน้ำนมดิบของโคนม 2. แนวทางการพัฒนาศักยภาพการผลิตโคนม จังหวัดสกลนคร ประกอบด้วย 2.1 การประชุมเชิงปฏิบัติการ 2.2 การนิเทศฟาร์มโคนม 3. ผลการพัฒนาศักยภาพการผลิตโคนม จังหวัดสกลนคร 3.1 ผลจากประชุมเชิงปฏิบัติการเพื่อพัฒนาศักยภาพการเลี้ยงโคนมของเกษตรกรผู้เลี้ยงโคนม จังหวัดสกลนคร มีความรู้ ความเข้าใจในด้านการผลิตโคนมหลังการฝึกอบรมเชิงปฏิบัติการสูงกว่าผลการประเมินการทดสอบก่อนการฝึกอบรมเชิงปฏิบัติการอย่างมีนัยสำคัญทางสถิติ (P<0.01) 3.2 การนิเทศฟาร์มโคนมในลักษณะการให้คำปรึกษาและการชี้แนะผสมผสานการเรียนรู้ร่วมกัน โดยการสังเกตและสัมภาษณ์ ปรากฏว่า เกษตรกรผู้เลี้ยงโคนมมีสมรรถภาพในการจัดการอาหารหยาบ อัตรากากรผสมติด และการจัดการสุขาภิบาลและการป้องกันโรคเต้านมอักเสบได้อย่างมีประสิทธิภาพ Abstract The purposes of this study were: 1) to investigate into state and problem in dairy farming industry in Sakon Nakhon province, 2) to find a potential development of dairy production in Sakon Nakhon province, and 3) to examine the potential development results of farmers’ dairy production in Sakon Nakhon province using action research. Target groups of this study included a group of 5 research participants and a group of 30 informants. The instruments used were a test, a questionnaire, an observation form, a structured interview, and a form for assessing the workshop. Analysis of quantitative data employed statistics of mean, percentage, standard deviation, and advancement percentage. Qualitative data were analyzed by content analysis. Data were classified and presented in the form of descriptive analysis. Findings of the study revealed as follows. 1. Results of investigating the state and problem in dairy farming in Sakon Nakhon province showed as follows: 1.1 The state: Dairy production of farmers in Sakon Nakhon province had a low production capacity. It could be observed from the indicators of amount of milk, milk composition and fertility in dairy cows. 1.2 The problem: Farmers’ lacked knowledge and understanding of dairy farming, such as selection and breeding, food and feeding, sanitary arrangement and disease prevention. Thus, it affected the milk yield of dairy cows. 2. A way to the potential development of dairy production in Sakon Nakhon province comprises: 2.1 workshops 2.2 supervision of dairy farms 3. Results from the potential development of dairy production in Sakon Nakhon province were as follows: 3.1 The result from the workshop on the potential development of dairy farming among cattle farmers in Sakon Nakhon province in order to have knowledge and understanding of dairy production showed that after the training they gained significantly higher knowledge and understanding than that before the training at the .01 level (p<.01). 3.2 The supervision of dairy farms in the manners of agricultural promotion, guidance and integration of learning together through the observation and interview appeared that dairy farmers had the capacity to manage roughage, conception rate, sanitation and prevention of mastitis efficiently.